Vulnerability assessment of the Croatian cyberspace to information warfare campaign via means of malicious websites comments - Dalibor Gernhardt (Strategos, 2020)
Influencing masses is one way of achieving military and political goals. As seen in the U.S. 2016 election campaign, adversaries are prepared to go great length to test new ways of battle. When event such as terrorist attack or natural disaster strikes, people are prone to believe anything they see without questioning the source or truthfulness of information. This work focuses on researching steps necessary to be performed by adversaries aiming to perform influence operation by method of placing malicious comments on websites. Potential adversary must evaluate target, identify most relevant websites and analyse commenting systems to make decision how to exploit them. Once adversaries choose course of action, their next step is creation of trustworthy, in this case Facebook profiles, which later can be used for malicious operations. For purpose of testing this methodology, vulnerability assessment of the Croatian webspace is performed, and Facebook as a dominant platform for writing comments is identified. In conclusion a formula for estimation of workforce required for creation and maintenance of false Facebook profiles is given. Knowledge about adversaries’ action is essential for effective defence in hybrid warfare environment.